1996
DOI: 10.1111/j.1939-1676.1996.tb02050.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antinuclear Antibodies by Indirect Immunofluorescence in Dog Sera: Comparison of Rat Liver Tissue and Human Epithelial‐2 Cells as Antigenic Substrate

Abstract: Rat liver sections and a human epithelial cell line (HEp-2) were compared as substrates for the detection of antinuclear antibodies (ANA) in the serum of normal dogs and dogs with suspected autoimmune disease, using a standard indirect immunofluorescence (IIF) technique. Antibody reactivity against rat hepatocyte nuclei was frequently found at low serum dilutions in normal dog sera. Using rat liver sections, a minimum significant positive titer, allowing negativity in more than 95% of normal dog sera, was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 6 publications
2
40
0
Order By: Relevance
“…The serum dilution 1:20 was chosen on the basis of positive reactions in 70/230 sera (31.3%) from dogs mainly with signs of systemic disease and 0/45 sera from healthy controls, both groups comprising different breeds. This corresponds well with what has been published by [11]. …”
Section: Methodssupporting
confidence: 93%
“…The serum dilution 1:20 was chosen on the basis of positive reactions in 70/230 sera (31.3%) from dogs mainly with signs of systemic disease and 0/45 sera from healthy controls, both groups comprising different breeds. This corresponds well with what has been published by [11]. …”
Section: Methodssupporting
confidence: 93%
“…The IIF‐ANA test is evaluated by fluorescence microscopy, in which different nuclear fluorescence patterns may allow subdivision of the results into different groups 4,5. In dogs, studies have shown that the use of monolayers of human tissue culture cells (eg, human epithelial‐2 [HEp‐2] cells) as a substrate in the assay makes it possible to divide ANA‐positive results into different subgroups 7,8. In humans, further determination of the specificity of IIF‐ANA–positive sera is used frequently to characterize the ANA reactivity.…”
mentioning
confidence: 99%
“…A commonly used method for such determination is the Ouchterlony immunodiffusion test 9,10. In ANA‐positive dogs, different immunodiffusion subgroups could be correlated to different ANA subgroups 7,8…”
mentioning
confidence: 99%
“…Serum samples from IMRD dogs had been collected in connection with other studies [2, 17, 18] and previously tested for the presence of ANA with IIF [19]. Samples were considered positive at a titre of ≥1:100.…”
Section: Resultsmentioning
confidence: 99%